PENGARUH INTERAKSI EDUKATIF GURU DAN SISWA TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN SOSIOLOGI DI KELAS XII IIS SMA KEMALA BHAYANGKARI - Issrotien Nasroh; Gusti Budjang; Imran Imran (Universitas Tanjungpura, 2017)
AbstractThe general problem in this research was how the influence of educational interaction of teachers and students to the motivation of learning on the subject of Sociology In Class XII IIS of Kemala Bhayangkari Senior High School. The research method used was descriptive method with the form of relationship studies. Total population 85 and sample 70. The data collecting technique used was indirect communication technique and documentation with data collection tool was questionnaire and note sheets from Kemala Bhayangkari senoir high school and data processing using Simple Linear Regression Analysis with SPSS computer aid version 16. The result of the data analysis shows that there was influence of Teacher and Student Interaction on Student Motivation Learning on Sociology Subject in Class XII IIS Kemala Bhayangkari senoir high school about 80% while the rest was influenced by other variables. Keywords: Educational Interaction of Teacher and Student, Learning Motivation